Maternal dietary intake and its associated socio demographic factors: evidence from Lahore, Pakistan. - Saeed, Ayesha; Humayun, Ayesha; Raana, Tahira (Progress in Nutrition, 2018)
Background: In developing countries, maternal under-nutrition is one of the causes of maternal morbidity and mortality. Good maternal nutritional status, resulting from long term dietary intake; also has great implications for neonatal health. The current study aimed at assessing the dietary intake of pregnant women and its associated socio demographic factors in Lahore, Pakistan. Methods: In a cross sectional survey 82 pregnant women were approached in a purposely selected tertiary care hospital in Lahore, Pakistan at the beginning of second trimester. Participants aged 19-45 years, were enrolled consecutively after taking written informed consent. Socio-demographics were recorded by a structured, pre-tested questionnaire. Maternal dietary intake was assessed by 24-hr Recall and Food Frequency Checklist. Data was collected from April-September 2013. Results were analyzed using SPSS version 21. Results: Mean age of the participants was 26 years, mean height was 157 cm, mean weight was 70 kg and mean BMI was 28.5 kg/m2. Self report decrease in dietary intake was 48% (n=39), while 33% (n=47) reported an increase and 62% (n=51) reported to be moderately active. Food frequency checklist revealed that chapatti was the staple; and 98% (n=81) consumed it daily. Data analysis of 24 hour recall highlighted that 98% (n=81) were unable to fulfill their caloric requirements. 91.5% (n=75) of the participants were consuming inadequately from vegetable group, 73.2% (n=60) from milk group, 63.3% (n=52) from fruit group, 26.8% (n=22) from cereal group and 25.3% (n=21) from meat group. Among age, education, employment, parity and income, it was revealed that age less than 24 years was associated with inadequate intake of all food groups and calories except meat intake although the association was not statistically significant. Conclusion: It was concluded that dietary intake of pregnant women in Pakistan is far from satisfactory. Antenatal nutritional counseling and mass media campaigns can be helpful in raising awareness.